Penerapan Psikologi Komunikasi Dalam Penyampaian Pesan Dakwah - Bagas Tri Cahyo; Akhmad Rifa’i (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Communication Psychology as a process of influencing and controlling the behavior of others through direct interaction. From this communication psychology, it will reveal the process to the results of learning activities, of course, through interaction to achieve the goal of realizing the process of delivering da'wah messages in the Qur'an Education Park (TPA) Baitul Qur'an Al-Hikmah. The purpose of this study is to understand intensively about the learning process, especially the interaction of teachers and students by considering psychological aspects due to the diverse ages and abilities of students. In data collection, the author uses a qualitative descriptive approach, namely describing the problem and the focus of the research. The methods carried out are interviews, observations, and documentation. From the analysis that the author explained, that TPA Baitul Qur'an Al Hikmah Bandar Lampung the process of applying communication psychology in delivering its da'wah message is very good, including formulating da'wah material, da'wah methods, and considering the psychological conditions of students. This Qur'an Education Park must be maintained because it is a place to educate qualified.